MANEVİ ZARARIN BELİRLENMESİ VE MANEVİ TAZMİNATIN HESAPLANMASI -TÜRK HUKUKUNA MANEVİ ZARARIN İKİ AŞAMALI OLARAK BELİRLENMESİNE İLİŞKİN BİR MODEL ÖNERİSİ- - (:unkn) unknown (My University, 2016)
Çalışmamızda manevi tazminatın yasal dayanakları incelenmiş olup, manevi zarara ilişkin yaklaşımlar ile manevi tazminatın fonksiyonu ve bunların manevi tazminatın belirlenmesindeki rolü ele alınmıştır. Ayırt etme gücü olmayan kişiler ile tüzel kişilerin manevi tazminat talepleri de ayrı bir başlık altında değerlendirilmiştir. Manevi tazminatın; telafi, tatmin, cezalandırma ve denkleştirme amaçları incelenerek, söz konusu amaçların manevi tazminatın belirlenmesindeki rolü açıklanmaya çalışılmıştır. Manevi tazminatın özellikleri ve bunların manevi tazminatın belirlenmesindeki rolünden bahsedilerek çalışma tamamlanmıştır.

In this article, the legal basis of moral damage, the function of moral damage and the role of these elements in order to determine moral damage are addressed. The moral damage claim of the people who have not ability to distinguish and the moral damage claim of the legal entity are examined in a seperate heading. The purpose of moral damage, namely; compensation, satisfaction, penalisition and equalising are analysed and the role of these purposes in order to determine moral damage are also explained. In conclusion, the features of moral damage and the role of these features in order to determine moral damage are indicated.
Determination of Moral Damages and Evaluation of Damages For Pain and Suffering Proposal for the Evaluation of Moral Damages in Two Stages in Turkish Law
Keywords: Hukuk